Cutaneous Adnexal Cylindroma of Breast: Epithelial Immunoreactivities for GATA-3, Mammaglobin, and E-Cadherin Do Not Equate to a Mammary Ductal Neoplasm - A. Halima; A. M. Pannunzio; E. M. Erstine; J. S. Ko; W. F. Bergfeld; R. M. Malaya; M. B. Frankel; B. C. Calhoun; C. D. Sturgis (Case Reports in Pathology)
Cylindromas are benign epithelial neoplasms derived from cutaneous eccrine adnexal structures. These tumors are most commonly encountered on the head, neck, and scalp of older women. In rare instances, solitary cylindromas may arise at other body sites. In the current case, a cylindroma of the skin of the breast was diagnosed by complete excision. Immunohistochemical studies confirmed the tumor cells to be immunoreactive with cytokeratin AE1/3, cytokeratin 5/6, cytokeratin 7, p63, and SOX10. The neoplastic cells were also noted to be immunoreactive with markers typically expected to be positive in ductal epithelium of the breast including GATA3, mammaglobin, and E-cadherin. The case emphasizes the importance of correlating clinical setting, imaging studies, patient history, and careful microscopic evaluation in arriving at an accurate diagnosis. This case also illustrates the point that not all “breast” tumors that are confirmed to be positive for GATA3, mammaglobin, and E-cadherin are derived from mammary ducts.